Análisis crítico de la aplicación del hábeas corpus “correctivo” en Ecuador - Erazo Merino, Johnny David (2023)
This paper is carried out from a critical perspective on the study of corrective habeas corpus in Ecuador, based on the analysis of the most significant sentences due to the possible arbitrariness with which they were granted by the operators of justice, where they are based on suffering physical abuse, threats to life and personal integrity or illnesses. In this sense, this guarantee in its corrective dimension, not only seeks the freedom of a person but also to adopt all the necessary means to ensure that there is a comprehensive reparation of the inmates in the centers of deprivation of liberty. The chapter began theoretically with conventional, constitutional and infra-constitutional regulation of habeas corpus, additionally with the typology of habeas corpus, its denaturalization and the case study of two sentences that caused social commotion.